Evaluation of the effect of aqueous Momordica charantia Linn. extract on zebrafish embryo model through acute toxicity assay assessment - Thiagarajan, Siroshini K.; Krishnan, Khamini Rama; Ei, Thandar; Shafie, Nurul Husna; Arapoc, Daryl J.; Bahari, Hasnah (Hindawi, 2019)
Momordica charantia Linn., commonly known as bitter gourd, has many protective roles due to its medicinal value as it contains bioactive components. However, this extract showed possible toxicity effect on zebrafish embryo. Thus this study was designed to differentiate the toxicity activities in two types of M. charantia sample which are Indian and Chinese M. charantia, as well as to compare between two different aqueous extraction methods, hot and cold aqueous method, using zebrafish embryo assay assessment. It was observed that the survival rate of zebrafish embryo decreased as the concentration of test extract increased for all samples of M. charantia. The LC50 values of hot aqueous Chinese M. charantia, hot aqueous Indian M. charantia, and cold aqueous Chinese M. charantia were 144.54 μg/ml, 199.53 μg/ml, and 251.19 μg/ml, respectively. However, cold aqueous Indian M. charantia has a higher LC50 which was not in the range of the tested concentration. Hatchability of Danio rerio embryo reduced as the concentration of M. charantia extract increased while no hatching was observed in the highest concentration (1000 μg/ml). Scoliosis of zebrafish larvae was only seen in higher concentrations (125-1000 μg/ml) of extract. The heartbeat of zebrafish larvae treated with M. charantia extract was within the normal range, 120-180 bpm, but at higher concentrations (125-1000 μg/ml) the heartbeat differed for all samples of test extract. Hence, although this plant extract was safe to be consumed due to its pharmaceutical effect, it still exhibited mild toxicity effect at higher concentration when it was evaluated on zebrafish embryo.